FEATURES OF HYDROCHEMICAL AND GEOCHEMICAL INDICATORS OF THE NORTH-EASTERN PART OF THE CASPIAN SEA (ZONES, OIL AND GAS FIELDS OF THE KAZAKHSTAN SECTOR) - D.Zh. Kalimanova; A.D. Kalimukasheva; J.A. Kubasheva; A.A. Nazhetova (Academic Scientific Journal of Chemistry, 2019)
Changes in hydrometeorological conditions that play a major role in the life of the Caspian Sea are combined with the impact on its ecosystem of economic activity, one of the types of which is pollution of the marine environment. Much attention is paid to environmental safety in the search and exploration of hydrocarbon deposits in the North Caspian, because without it, neither its high biological productivity, nor the fishery value can be maintained. The Caspian Sea, and especially its northern shallow part, is a highly productive body of water. Such extremely high productivity of the Caspian is combined with the relative poverty of the biological diversity of this reservoir. A significant part of the Caspian hydrobionts is relict. This part of the sea is the richest in biological productivity. And it is not by chance that the rich nutrients and the organic substrate of the waters of the Northern Caspian have a great influence on the diversity of the flora and fauna of the entire Caspian. However, at present, the Caspian Sea and especially the Northern Sea, like the other seas of the world, are experiencing increasing anthropogenic impact, which is manifested in pollution with oil products and heavy metals, as well as in active shipping and hydro-construction.